2021
DOI: 10.1098/rsos.201883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B-site Co substitution on the structure and magnetic properties of nanocrystalline neodymium orthoferrite synthesized by auto-combustion

Abstract: Samples of cobalt-doped neodymium orthoferrite compounds, NdCo x Fe 1−x O 3 (0.0 ≤ x ≤ 0.5) were synthesized via glycine auto-combustion between 250 and 300°C and calcined at 500°C for 2 h. X-ray diffraction showed that all compounds had an orthorhombic perovskite structure with space group Pbnm. Increasing cobalt doping gradually reduced the lattice parameters and contracted the unit cell volume. Both X-ray diffraction and scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…The substitution of smaller La 3+ by larger Sr 2+ caused growth of the cell along the c axis. The introduction of Co 2+ decreased the volume of the unit cell, which was consistent with the literature. …”
Section: Resultssupporting
confidence: 90%
“…The substitution of smaller La 3+ by larger Sr 2+ caused growth of the cell along the c axis. The introduction of Co 2+ decreased the volume of the unit cell, which was consistent with the literature. …”
Section: Resultssupporting
confidence: 90%
“…Since the ionic radius of Co 3+ (54.5 pm in LS and 61.0 pm in HS) is slightly less than that of Fe 3+ (64.5 pm in HS), shrinkage is expected, indicating a successful substitution of Co ions at Fe sites [17,36,37]. Similar results have also been reported for NdFe 1−x Co x O 3 systems [24][25][26]. In order to explore the effect of Co doping on the fine structure of the parent LFO, we performed FTIR spectroscopy, an analytical technique capable of revealing the nature of structures by detecting lattice vibrations.…”
Section: Preparation Of Co-doped Lufeo 3 Powders and Structure Analysissupporting
confidence: 76%
“…Recently, researchers have carried out extensive investigations on the structure, morphology, and electrical, optical, and magnetic properties of B-site cobalt-doped orthorhombic RFeO 3 . Most research focuses on orthorhombic NdFeO 3 [24][25][26][27][28], YbFeO 3 [29], DyFeO 3 [30], and LaFeO 3 [31]. It has been found that these Co-doped RFeO 3 systems show considerable enhancement in their physical properties compared to their parent counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Hexaferrite exhibits magnetic properties and it can be used in recording devices and in permanent magnetic materials [21]. SrFe nanoparticles have potential magnetic applications in magnetic storage, logic, and data storage [42].…”
Section: Vsm Analysismentioning
confidence: 99%
“…TG-DTA graph of M-SrFe Nps 5.489 mg of the sample underwent the experimental analysis, which was conducted while it was being heated at a temperature of 20 0 C per minute in an air medium. The temperature range is between 30 0 C and 1200 0 C. The weight loss of 1.84% begins at temperatures between 300 0 C and 122 0 C. This is due to the partial vaporization of the compound[47]. The weight loss of 1.8% occurs at 460 0 C due to the formation of Fe2O3[48].…”
mentioning
confidence: 99%